PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD UNTUK PENINGKATAN KETERAMPILAN BERBICARA PADA PESERTA DIDIK KELAS II SD - Irine Amalia Sinta Balqis; Sukarir Nuryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this research is to design an instructional tool in the form of flashcards that supports the enhancement of formal oral communication skills among second-grade primary school learners. The main issue addressed is the students’ low mastery of standard vocabulary, which affects their ability to express ideas orally using appropriate formal language. This research utilized a The Research and Development (R&D) approach was carried out following the ADDIE model, which consists of five key stages: analyzing needs, designing the product, developing materials, applying them in real settings, and conducting evaluations. The participants in this study were 32 students enrolled in the second grade. from SD Negeri Salamsari. Instruments included expert validation sheets, pretest and posttest questions, student and teacher response questionnaires, and interview guidelines. Validation results showed that the media was feasible, with material validation scoring 80% and media validation scoring 90%. The flashcard product, named FLASIFA (Flashcard of Adjective Vocabulary), significantly improved learning outcomes, with pretest and posttest average scores of 42.84 and 87.31, respectively. Findings from the paired sample t-test demonstrated a meaningful statistical distinction between the compared data sets, while the N-Gain value of 0.7865 was classified as high. Both teachers and students expressed highly favorable responses toward the use of the media. were also highly positive. Thus, FLASIFA is proven to be a feasible and effective medium to enhance standard speaking skills among second-grade elementary students.